Digital Data Streams: Creating Value from the Real-Time Flow of Big Data. (May 2016) - Pigni, Federico; Piccoli, Gabriele; Watson, Richard
There is no escaping the Big Data hype. Vendors are peddling Big Data solutions; consulting firms employ Big Data specialists; Big Data conferences are aplenty. There is a rush to extract golden nuggets (of insight) from mountains (of data). By focusing merely on the mountain (of Big Data), these adventurers are overlooking the source of the revolution—namely, the many digital data streams (DDSs) that create Big Data—and the opportunity to improve real-time decision making. This article discusses the characteristics of DDSs, describes their common structure, and offers guidelines to enable firms to profit from their untapped potential.